The experiential learning model based on household waste for the understanding of plant cell concepts - Sitti Aisyah; Ardiansyah Ardiansyah; Indri Pratiwi (STKIP Persada Khatulistiwa Sintang, 2026)
The persistent weakness in students' mastery of plant cell concepts indicates a structural problem in conventional science instruction, particularly the lack of direct conceptual construction experiences. The purpose of this study is to determine whether the experiential learning model based on household waste affects students' conceptual understanding of plant cell material. This study examines the impact of experiential learning using improvised microscopes assembled from household waste materials on eighth-grade students at MTs Negeri 3 Kota Palu. The research employed a quasi-experimental method with a non-equivalent control group design. Two classes were purposively selected: class VIII F as the experimental group and class VIII H as the control group. Data were collected through pre-test and post-test essay instruments aligned with conceptual understanding indicators. Statistical analysis showed a significant effect, indicated by an independent sample t-test significance value of 0.000, below the 0.05 level. The experimental group obtained higher mean post-test scores than the control group, demonstrating that experiential learning supported by simple waste-based microscopes effectively improves students' conceptual understanding of plant cells in science learning.